Left hemothorax: an unusual complication of delayed right ventricular perforation by a permanent pacemaker lead - Pojar, Marek; Voborník, Martin; Nový, Jiří (Journal of cardiac surgery, 2013)
Cardiac ventricle perforation by a pacemaker (PM) lead is an uncommon complication of PM implantation. We report a patient with a delayed right ventricular perforation from a permanent PM lead which presented as a left hemothorax.
Keywords: implantované elektrody; počítačová rentgenová tomografie; hemotorax; polytetrafluoroethylen; Humans; odstranění implantátu; pleura; Heart Failure; srdeční selhání; cizí tělesa; Pericardium; Shock, Cardiogenic; Aged; Hemothorax; Foreign Bodies; senioři; lidé; kardiogenní šok; Pleura; Polytetrafluoroethylene; Cardiomyopathy, Dilated; Device Removal; Biocompatible Materials; perikard; Electrodes, Implanted; Male; šicí techniky; Tomography, X-Ray Computed; defibrilátory implantabilní; Heart Ventricles; biokompatibilní materiály; Suture Techniques; Defibrillators, Implantable; mužské pohlaví; srdeční komory; dilatační kardiomyopatie